Selective growth of znic oxide nanowires on the metal electrodes - Choi, Young-Jin; Park, Jae-Hwan; Park, Jae-Gwan (Journal of electroceramics, 2006)
Although nanowires have been attractive subject of numerous researches due to their fascinating features, their compatibilities with industrial aspects of semiconductor technology should be considered for further progress. In this regard, the selective growth of nanowires on typical electrodes of semiconductor industry would be a step forward. In this study, we studied growth and alignment of ZnO nanowires on the desired position on several kinds of electrodes. As typical electrode materials aluminum, titanium, and platinum were considered. For patterned growth of ZnO nanowires on the selective area of Al, Ti, and Pt electrodes, Au catalytic layer was deposited on the desired position of the electrodes and the optimized processing conditions that the nanowires could be grown only where the patterned catalytic layer present were thoroughly examined.